(untitled) (Scientific journal of the Fergana State University, 2025)
The article discusses the theoretical and methodological foundations for developing professional competence in future teachers through creative-pedagogical approaches. It outlines the technological system for enhancing professional competence based on creative-pedagogical methods and examines the effectiveness of these approaches in the training of future educators. Additionally, it analyzes the opportunities provided by creative-pedagogical approaches in the preparation of future teachers.